PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP REVISIT INTENTION PADA HOTEL THE ORIENT JAKARTA - Ignasius Richard Linanto; Dewanta Facrureza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of Customer Relationship Management (CRM) on revisit intention at The Orient Hotel Jakarta. The independent variable is CRM, measured through four dimensions — service quality, communication, trust, and commitment — while the dependent variable is revisit intention. The study was motivated by the suboptimal CRM implementation at the hotel, reflected in guest complaints regarding service quality, the absence of a membership program, and limited personal communication with guests. A quantitative descriptive approach was employed, with data collected via a 1–4 Likert scale questionnaire. The sample consisted of 100 respondents who had previously stayed at The Orient Hotel Jakarta within the past year, determined using the Slovin formula from a population of 23,567 guests. Data were analyzed using IBM SPSS version 25 through validity and reliability tests, classical assumption tests, T-test, F-test, simple linear regression, and coefficient of determination. The results indicate that all four CRM dimensions, service quality, communication, trust, and commitment, each have a significant partial effect on revisit intention. Simultaneously, CRM has a significant effect on revisit intention with an F-value of 133.799 and a significance level of 0.000. The coefficient of determination of 57.7% indicates that CRM moderately explains the variation in revisit intention, while the remaining 42.3% is attributed to other factors outside the model.